DNA Repair Mechanism Operating during Cell Cycle Checkpoints in Eukaryotic Cells: A Briefly Review - Asimuddin, M.; Jamil, K. (Highlights on Medicine and Medical Research Vol. 13, 2021)
In this article, we have briefly reviewed the molecular mechanism involved in DNA damage and repair at various checkpoints of the cell cycle in eukaryotic cells. Eukaryotic cells have an ability to develop a response to DNA damage that can be caused by environmental factors such as chemicals, xenobiotics, free radicals, ionizing radiation (IR) or products of intracellular metabolism and also due to products of medical therapy. In response to these insults, the following reactions can take place in the cellular environment: (a) In the case of DNA damage, the protein machinery is activated and attaches itself to the site of the lesion which results in cell cycle arrest at the G1 to S phase (the G1/S checkpoint), DNA replication phase (the intra-S checkpoint), or G2 to mitosis phase (the G2/M checkpoint) until the lesion undergoes repair; (b) As there are many different lesions possible, the following DNA repair mechanisms are activated which include direct repair, base excision repair, nucleotide excision repair, mismatch repair, and double strand breaks (DSBs) such as, homologous recombination (HR) and non-homologous end-joining (NHEJ) repair. In HR, the most important emerging proteins are the tumor suppressor proteins BRCA1, BRCA2, and Rad51 which play an important role in maintaining the genomic integrity by protecting cells from double strand breaks. Therefore, it is important to identify the functional role of BRCA1 and BRCA2 proteins which will then be helpful in designing specific drugs in targeting solid tumors. Furthermore, interaction of Rad51 with BRCA2 protein complexes are essential for HR, which can be visualized by microscope as a foci and are thought to be representative sites where repair mechanism can take place. In addition, we have given special focus to the recent finding in the interaction of Rad51 with BRCA2 protein in double strand breaks by HR.